Formulation of agenda 21 process indicators for Malaysia - Ngah, Kamaruddin; Mustaffa, Jamaludin; Zakaria, Zaherawati; Noordin, Nazni; Mohamed Sawal, Mohd Zool Hilmie (Canadian Center of Science and Education, 2011)
This paper consists of formulation of Agenda 21 progress indicators for Malaysia from its establishment in 1992 which calls on countries, organizations and non governmental organizations to develop and use indicators of sustainable development. It provides a firm basis for decision-making on the impacts of economic activities on the environment that have to be clearly understood and taken into account. The initiatives taken by Malaysia in response to the needs identified in Agenda 21 as well as those identified through its own development planning, monitoring system and development plans. Also included are initiatives undertaken by the Federal Government, by the State Government of Selangor, and by non-governmental organizations. The approach adopted by each category of stakeholder is unique but appropriate to the mandate and modus operandi of the relevant organization. Policy- and decision-makers are becoming increasingly aware of the need to address the uncertainties and complexities of Agenda 21 more realistically. In order to do this, progress indicators must reflect the nature of relationships between disparate issues adequately. In future, the development and use of indicators to assess progress towards fulfilling the nation’s Agenda 21 requires continual commitment and activities. The development of such indicators requires the participation of policy- and decision-makers, scientists, international organizations, and a knowledgeable public to work together in a joint initiative that would result in better-informed choices of indicators that capture the inter-linkages between sectors towards achieving national Agenda 21 targets.